Increasing Hormonal Control of Skeletal Development: An Evolutionary Trend in Amphibians - Vassilieva, Anna B.; Smirnov, Sergei V. (Frontiers in Ecology and Evolution, 2021)
The biphasic life history of amphibians includes metamorphosis, a complex developmental event that involves drastic changes in the morphology, physiology and biochemistry accompanying the transition from the larval to adult stage of development. Thyroid hormones (THs) are widely known to orchestrate this remodelling and, in particular, to mediate the development of the bony skeleton, which is a model system in evolutionary morphological studies of amphibians. Detailed experimental studies of the role of THs in the craniogenesis of diverse urodelan amphibians revealed that i) these hormones affect both the timing and sequence of bone formation, ii) TH involvement increases in parallel with the increase in divergence between larval and adult skull morphology, and iii) among urodelans, TH-involvement in skull development changes from a minimum in basal salamanders (Hynobiidae) to the most pronounced in derived ones (Salamandridae and Plethodontidae). Given the increasing regulatory function of THs in urodelan evolution, we hypothesized a stronger involvement of THs in the control of skeletogenesis in anurans with their most complex and dramatic metamorphosis among all amphibians. Our experimental study of skeletal development in the hypo- and hyperthyroid yellow-bellied toad (Bombina variegata: Bombinatoridae) supports the greater involvement of THs in the mediation of all stages of anuran cranial and postcranial bones formation. Similar to urodelans, B. variegata displays enhancing TH involvement in the development of cranial bones that arise during larval ontogeny: while the hormonal impact on early larval ossifications is minimal, the skull bones forming during metamorphosis are strictly TH-inducible. However, in contrast to urodelans, all cranial bones, including the earliest to form, are TH-dependent in B. variegata; moreover, the development of all elements of the axial and limb skeleton is affected by THs. The more accentuated hormonal control of skeletogenesis in B. variegata demonstrates the advanced regulatory and inductive function of THs in the orchestration of anuran metamorphosis. Based on these findings, we discuss i) changes in THs function in amphibian evolution and ii) the role of THs in the evolution of life histories in amphibians.